Photochemical Redox Cycling of Naphthoquinones Mediated by Methylene Blue and Pheophorbide A - Lisa M. Landino; Joseph A. Reed (Molecules)
The photoreduction of plastoquinone, a para-benzoquinone, by chlorophyll initiates photosynthesis in chloroplasts. The direct photoreduction of biologically relevant quinones by dietary chlorophyll metabolites has been reported and may influence health outcomes. We examined red light-mediated photoreduction of ortho- and para-naphthoquinones including vitamin K3 using the photosensitizers methylene blue and pheophorbide A, a chlorophyll metabolite. Naphthoquinone reduction was monitored by UV/Visible spectroscopy and required a photosensitizer, red light and a tertiary amine electron donor. Combinations of methylene blue and ethylenediaminetetraacetic acid or pheophorbide A and triethanolamine in 20% dimethylformamide were employed for all photoreduction experiments. Hydrogen peroxide was generated during the photochemical reactions by singlet oxygen-dependent oxidation of the reduced naphthoquinones. Hydrogen peroxide was quantified with horseradish peroxidase following irradiation; the reduced naphthoquinones acted as peroxidase co-substrates. Histidine, a singlet oxygen scavenger, enhanced the rate of photoreduction by limiting the re-oxidation process. Catalase slowed the rate of photoreduction by regenerating molecular oxygen from hydrogen peroxide so that it could be photoexcited to singlet oxygen. The rates and extent of naphthoquinone photoreduction were dependent on molecular oxygen exposure in different reaction formats including in a cuvette and a plate well. Reduction of the tetrazolium salt MTT to the formazan via electron transfer from the photoreduced quinones was also used to quantitate the extent of photoreduction.